2022
DOI: 10.1186/s40337-022-00551-8
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with active anorexia nervosa: a systematic review

Abstract: Background It is a common misconception that women with active anorexia nervosa (AN) are less likely to conceive. Pregnancies in women with AN are considered high risk. The purpose of this systematic review was to explore pregnancy complications in women with active AN, including maternal, fetal, and neonatal complications. Methods The authors conducted a systematic review in accordance with PRISMA statement guidelines with stringent selection crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The results on AN and LBW are consistent with a 2014 systematic review and meta-analysis showing that AN was associated with a lower birth weight (standardised mean difference −0.19 kg [95% CI −0.25, −0.15]) [41]. The present findings are also in agreement with the systematic review by Pan et al, in which the authors concluded that SGA and LBW were some of the most reported pregnancy complications in women with active AN [40]. Low pre-pregnancy BMI is a risk factor in women with AN for delivering an LBW infant [34].…”
Section: Review / La Revuesupporting
confidence: 93%
See 1 more Smart Citation
“…The results on AN and LBW are consistent with a 2014 systematic review and meta-analysis showing that AN was associated with a lower birth weight (standardised mean difference −0.19 kg [95% CI −0.25, −0.15]) [41]. The present findings are also in agreement with the systematic review by Pan et al, in which the authors concluded that SGA and LBW were some of the most reported pregnancy complications in women with active AN [40]. Low pre-pregnancy BMI is a risk factor in women with AN for delivering an LBW infant [34].…”
Section: Review / La Revuesupporting
confidence: 93%
“…The analysis of past and current AN as a single group may have also influenced the results of the analysis on PTB. A systematic review by Pan et al found that PTB was among the most commonly reported complications in pregnant women with active AN [40]. The meta-analysis shows a significant positive association between BN and PTB but not AN and PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, it would be of interest to determine the trajectory of weight gain depending on the aetiology of underweight, e.g., constitutive thinness, anorexia nervosa, or orthorexia. A recent systemic review suggested that active anorexia nervosa could be associated with adverse pregnancy outcomes including prematurity, intrauterine growth restriction, or low birth weight [ 21 ]. In a case series, it was shown that women with active anorexia nervosa had a lower weight gain and newborns with lower birth weight than women in remission from eating disorders [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…those with eating disorders or medical disorders affecting nutrition, should be considered at increased risk and serial USS undertaken. 53…”
Section: [Evidence Level 2+]mentioning
confidence: 99%
“…Therefore, women with a low BMI at booking (below 18.5 kg/m 2 ) and who have features which indicate that the maternal stature is not physiological, e.g. those with eating disorders or medical disorders affecting nutrition, should be considered at increased risk and serial USS undertaken 53 . [Evidence level 2++]…”
Section: What Are the Risk Factors For Fetal Growth Disorders In Preg...mentioning
confidence: 99%